Gross Anatomical Studies on the Tibia and Fibula of Rhesus Monkey (Macaca mulatta) - Kamal Sarma (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the tibia and fibula bones obtained from carcass of one adult rhesus monkey. The tibia bone was a long, thick prismatic bone. Shaft was 3 sided throughout its proximal half. Distal end was cylindrical. Lateral surface presented a shallow sulcus muscularis. Caudal surface had a single indistinct rd popliteal line. Medial surface was slightly convex up to distal 3 of its length. The nutrient foramen was located in rd th upper 3 of tibia close to the lateral border. Anterior border was prominent in its upper 4 and constituted the tibial crest. The distal extremity was quadrilateral in outline. It presented two deep antero-posterior grooves separated by a ridge. Fibula was laterally compressed bone lateral to the tibia. It consisted of a proximal head, shaft and distally lateral malleolus. Tibial index was recorded as 0.05. Tibial platymeric index was found to be 0.56. Tibial mid-shaft index represented the ratio of tibial proximal condyles to its shaft. It was 0.28. Distal tibial index was recorded as 0.85.